Analisis Faktor – Faktor yang Mempengaruhi Nilai Perusahaan Manufaktur dengan ROA Sebagai Variabel Intervening (Studi pada Perusahaan Manufaktur food and beverages yang Listed di BEI tahun 2010-2012) - Satriya, Brian Yuanta; Wahyudi, Sugeng (Diponegoro Journal of Management, 2017)
The value of the company is a factor that considered by investors in taking investment decision. Research by Sulistyawan (2005), and Hermawati (2011)  shows there are differences in the results based on existing data, there relationship that might be differences of  affect the value of the company.  Therefore,it is needed for further research. This study tested the effect of Sales growth (SG), Total Asset Turnover (TATO), Net Profit Margin (NPM) against the Return on Asset (ROA) as well as the influence of Return on Assets (ROA), Sales growth (SG) against Price Book Value (PBV) on food and baverage manufacturing company that is listed on the Indonesia stock exchange (idx) of the period 2010 – 2012. The sample used in this study consisted of 20 food and baverage manufacturing company that is listed on the Indonesia stock exchange (idx) of the period 2010 – 2012. Its purposive sampling. The data obtained from Indonesian Capitan Market Directory (ICMD) and the Annual Report of the company. Analytical techniques used is multiple regression analysis and path analysis of SEM programs.  The results showed that Sales growth (SG) have a negative effect of the Return on Assets (ROA), as well as direct negative and significant effect on Price Book Value (PBV) also. Total Asset Turnover (TATO) have a negative effect of the Return on Assets (ROA). Net Profit Margin (NPM) have a positive and significant effect of the Return on Asset (ROA).  Return on Asset (ROA) have a positive and significant effect of the Price Book Value (PBV).